Grating optical diffraction radiation - Promising technique for non-invasive beam diagnostics; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 201, iss. 1 : Radiation from Relativistic Electrons in Periodic Structures (RREPS '01) - Karataev P. V. Pavel Vladimirovich; Araki S.; Hamatsu R.; Hayano H.; Hirose T.; Muto T.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Urakawa J. (2003, 2003)
Title screen